2019
DOI: 10.1186/s12913-019-4150-x
|View full text |Cite
|
Sign up to set email alerts
|

Social psychological mechanisms and processes in a novel, health professional-led, self-management intervention for older stroke individuals: a synthesis and phenomenological study

Abstract: Background A good portion of stroke patients in Western countries are over 65 of age. Because of sequelae, they often lead more isolated lives after the stroke. In terms of social reintegration, this group of patients is especially vulnerable. Reintegration into the community post-stroke greatly depends on support from family. However, the stroke individual’s closest relatives are at risk of becoming overburdened. The objectives are to describe the social psychological mechanisms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This could, in turn, alleviate their emotional distress and improve their physical and psychosocial QoL. It would also be beneficial to establish social support networks through mentorship schemes ( 53 , 54 ) and to encourage stroke survivors to proactively use this support as a resource and source of motivation during the recovery process.…”
Section: Discussionmentioning
confidence: 99%
“…This could, in turn, alleviate their emotional distress and improve their physical and psychosocial QoL. It would also be beneficial to establish social support networks through mentorship schemes ( 53 , 54 ) and to encourage stroke survivors to proactively use this support as a resource and source of motivation during the recovery process.…”
Section: Discussionmentioning
confidence: 99%
“…Often, the support for the changes required to achieve the goals established by the participant and the case manager, is given by the family members, who provide the motivation and the help to adapt daily activities. Thus, the rehabilitation process must address both patients and caregivers, since the consequences of the stroke affect everyone (24) . Results from a Scottish study showed that the treatment of post-stroke patients was less difficult when it was shared with family and friends, who provide emotional support and assistance in daily living activities, increasing the patient's security to make decisions (25) .…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that family involvement in self-management is frequently identified as a strategy to improve an individual's engagement; however, families may become overly involved and limit opportunities for patients to practise self-management behaviours [14,30,32,[37][38][39]. Families who are willing to support self-management outside of the therapistdriven sessions provide greater opportunity for patients to master self-management skills within the hospital setting [40], which is particularly valuable for time-poor clinicians [17].…”
Section: Discussionmentioning
confidence: 99%